PEMBERDAYAAN KARANG TARUNA DI KELURAHAN MATALI KECAMATAN KOTAMOBAGU TIMUR - MAKALALAG, DICKY WAHYUDI; RORONG, ARIE JUNUS; RURU, JOORIE MARHAEN (Sam Ratulangi University, 2019)
Karang Taruna is a youth organization in the village as a place to develop self potential in the field of social welfare business. As a youth organization, youth cadets are guided by basic guidelines where the management structure and tenure of each region from village to national level have been arranged. All of these are manifestations of organizational regeneration for the advancement and continuation of organizations and fostering youth members both in the present and in the future. Empowerment is to eliminate all unnecessary rules, procedures, orders, etc. which hinder the organization from achieving its objectives. The organization is a social unit established by humans in a relatively long period of time, consisting of a group of humans of at least two people, having coordinated, organized and structured activities, established to achieve certain goals of having an identity that distinguishes one entity from another . This study uses a type of qualitative research in which this research is descriptive, namely conducting in-depth interviews of primary data collection and secondary data collection, which then results of primary and secondary data is processed and data will be obtained. The results showed that creating an atmosphere or climate that enabled the potential of human resources to develop in the village of Matali, the potential that could be developed was from the youth of Matali Village, namely in terms of sports and also religious aspects where sports could provide opportunities for the Matali village youth to participate and excel in the sports arena as well as religious aspects can make the youth of Matali Village become more religious. Empowerment of cadets in Matali Village is overseen by the government and the community and also with the existence of youth clubs providing protection by involving or embracing young people or communities of Matali Village both from the middle to lower classes and above all embraced so as to contribute together and so that also not impressed this youth only in certain groups or upper class only. The potential and power possessed by the community of Matali Village is more specifically the Matali youth that can be channeled and can continue to be developed with the programs made by the youths of the Matali Village.Keywords: Empowerment, Organization, Youth Organization